Descentralização fiscal no Brasil: economia e finanças públicas nos municípios alagoanos (1999/2010) - Araújo, Anderson Henrique dos Santos (2013)
The present work aims to study the public finances and the economic behavior of Municipalities alagoanos between the years 1999/2010, using the fiscal and economic indicators commonly used. Therefore, it is considered the theoretical training of Public Finance, the influence of government in the economy to theoretical assumptions about the process of decentralization / centralization in Brazil. The Constitution of 1988 is a milestone in the pursuit of decentralized fiscal federalism, since from that moment, the municipalities now receive the status of a federated entity and had the largest increase in revenues and collection mechanisms itself. Thus, subnational, closer to the wishes of the population could more effectively meet the state's role in the production of public goods and the solution of the demands of the population. However, in the years after the Constitution of 1988, the political changes in the country, especially with Brazil's adherence to the neoliberal project, the advent of the plan and the actual enactment of the Fiscal Responsibility Law, led to a new process of fiscal centralization in Brazil, with consequences for the 5565 Brazilian municipalities. In this context, it is statistically analyzed the finances and economy of the municipalities in Alagoas. The GDP of them indicate the growth of the service sector and centralization of wealth in a small number of cities, as well as the lack of dynamics in small towns, which the government has the primary component in your product. The analysis of municipal finances, with the support of development indicators and the index itself FIRJAN fiscal management, confirm the initial assumptions of the work: the low collection itself, high dependence on federal transfers, effort and compliance with the limits established by LRF for personnel expenses and low levels of investment. Thus, the main findings indicate that the decentralization process of the 1988 Constitution was undermined by the next decade, penalizing the poorest municipalities in case of most in Alagoas.